Chip formation and hole quality in dry drilling additive manufactured Ti6Al4V. Issue 1 (2nd January 2020) - Ming, Weiwei; Dang, Jiaqiang; An, Qinglong; Chen, Ming
ABSTRACT: Dry drilling known as a sustainable and complicated machining operation is usually involved in many applications of titanium alloys. Previous studies have demonstrated that different surface qualities of the drilled holes influence the service performance and the final fatigue limit of the parts. However, a comprehensive understanding of their origins in terms of the generated chips and thereby microstructures of hole surfaces is not widely reported but is of great importance. To this end, this work addresses the typical characteristics of produced chips and drilled holes induced by the drilling operation with a macro-micro combination view. A particular focus was put on the chip morphology and chip evolution and surface integrity of drilled holes with the commonly used standard twist drill during dry drilling process. The results show that the chips show different morphologies with the advancement of drill bit and continuous chips were obtained regardless of the cutting variables. As the drill progressed, chip morphology was transferred from spiral cone to folded ribbon. Some scratch and smearing traces were formed on the hole surfaces due to the tangled chips on the drill bit. Furthermore, the grains in the hole wall vicinity present different morphologies when observing the cross-section of drilled holes and a nanocrystalline structure appears close to the drilled hole surface.